Non-human primate models of human respiratory infections. (July 2021) - Lemaitre, Julien; Naninck, Thibaut; Delache, Benoît; Creppy, Justina; Huber, Philippe; Holzapfel, Marion; Bouillier, Camille; Contreras, Vanessa; Martinon, Frédéric; Kahlaoui, Nidhal; Pascal, Quentin; Tricot, Sabine; et al.
Highlights: NHPs represent the best animal model for human immunology and for the major respiratory infections pathophysiology. NHPs allow controlled pathogen exposure and monitoring, which facilitates treatments and vaccines evaluation. Whole-body imaging allows respiratory infectious diseases monitoring in NHP in a very similar way to humans. Abstract: Respiratory pathogens represent a great burden for humanity and a potential source of new pandemics, as illustrated by the recent emergence of coronavirus disease 2019 (COVID-19). In recent decades, biotechnological advances have led to the development of numerous innovative therapeutic molecules and vaccine immunogens. However, we still lack effective treatments and vaccines against many respiratory pathogens. More than ever, there is a need for a fast, predictive, preclinical pipeline, to keep pace with emerging diseases. Animal models are key for the preclinical development of disease management strategies. The predictive value of these models depends on their ability to reproduce the features of the human disease, the mode of transmission of the infectious agent and the availability of technologies for monitoring infection. This review focuses on the use of non-human primates as relevant preclinical models for the development of prevention and treatment for human respiratory infections.